A LQR Optimal Method to Control the Position of an Overhead Crane - J. Jafari; M. Ghazal; M. Nazemizadeh (IAES International Journal of Robotics and Automation (IJRA), 2014)
In this paper, a LQR (Linear Quadratic Regulation) optimal method is implemented to control position of an overhead carne. To do this, a tracking formulation of LQR is developed and applied to the system. Hence the dynamic model of the overhead crane is presented, the dynamic of the actuator motor of the trolley is considered. As the parameters of the optimal controller assigned, some simulations are done to show the efficiency of the proposed method.